Acellular fish skin matrix on thin-skin graft donor sites: a preliminary study. (2nd September 2019) - Badois, Nathalie; Bauër, Pierre; Cheron, Maxime; Hoffmann, Caroline; Nicodeme, Marguerite; Choussy, Olivier; Lesnik, Maria; Poitrine, Florence Canoui; Fromantin, Isabelle
Abstract : Objective: Surgery for head and neck cancer often requires free flap reconstructions, whose harvesting site often requires a thin-skin graft. Wounds from the thin-skin donor site are comparable to an intermediate or deep second-degree burn. This is uncomfortable and can lead to complications such as a long healing time, local infections and pain. Since they are reproducible, these wounds may serve as a model for an objective assessment of new healing medical devices. The acellular fish skin matrix is a new medical device designed to improve healing quality and time. Methods: We compared the outcomes between standard procedure and the use of this matrix placed on the split-thickness skin graft (STSG) donor site, in patients operated on in our centre for radial forearm free flap reconstruction for head and neck wounds. Results: There were 21 patients included. The healing time was halved when using the acellular fish skin matrix, from 68 to 32 days on average. Acellular fish skin matrix reduced pain levels and local infection. The visual analogue pain scale (VAS) was ≥3 at five days (p=0.0034) and infection rate reduced from 60% to 0% (p=0.0039). Conclusion: These results are extremely encouraging. However, it is important to take into account the relatively high cost of this matrix for its future indications. A larger study including an overall cost estimation and an assessment on different wound types would be interesting, to better target the indications of the acellular fish skin matrix.